Non-destructive method for estimating chrysanthemum leaf area - Toshik I. da Silva; João E. da S. Ribeiro; Marlon G. Dias; Renata R. P. Cruz; Larissa F. Macêdo; Jackson S. Nóbrega; Giuliana N. B. Sales; Erli P. dos Santos; Franciscleudo B. da Costa; José A. S. Grossi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Chrysanthemum (Dendranthema grandiflora) is the second most produced and commercialized ornamental plant in the world. Measuring leaf area through non-destructive methods is fundamental for studies on its growth and production. The estimation of leaf area by linear dimensions of the leaves can be a strategy for this purpose. The objective of this study was to find allometric equations to estimate the leaf area of chrysanthemum. The linear, linear without intercept, quadratic, cubic, power, and exponential regression models were used for the analysis. The choice of equations was based on the highest coefficients of determination. The non-destructive method using allometric models has accuracy for estimating the leaf area (LA) of chrysanthemum from the product between leaf length (L) and leaf width (W). The LA of chrysanthemum can be estimated using the equation ŷ = 0.6611*LW0.9490 (L - leaf length; W - leaf width). This equation will allow researchers and producers to determine leaf area non-destructively.